Analysis of application of back-to-back HVDC system in Tomsk electric power system - Ruslan Ufa; Alexandr Gusev; Ahmed A. Zaki Diab; Aleksey Suvorov; Nikolay Ruban; Mikhail Andreev; Alisher Askarov; Vladimir Rudnik; Omer Abdalla; Ziad M. Ali; Ahmed Ibrahim; Raef Aboelsaud (Energy Reports, 2020)
In this article the research results of application of back-to-back HVDC system in the Tomsk electric power system are presented. Historically, power transmission between the South to the North parts of the Tomsk electric power system is realized via the long double-circuit 220 kV overhead transmission line. However, due to electrical load increasing and growing complexity of the grid, as well as the length (about 800 km) and low transfer capacity of this transit, it cannot be used as a reliable link for parallel operation of these parts, as a consequence, there is an operational section at this transit. To solve this task, the back-to-back HVDC system is proposed to provide an asynchronous link for parallel operation of these parts. Therefore, appropriate studies and calculations were performed, in particular the optimal location and sizing of back-to-back HVDC system were defined. Extra researches of back-to-back HVDC's impact on emergency scenarios of Tomsk electric power system power are conducted. It is shown, that its installation decreases the level of short-circuit current and oscillations in electric power system, and as a result increases the stability of load operation, especially motor load.
Keywords: 330; Asynchronous interconnection; Back-to-back HVDC system; Electric power system; Planning; Sizing